Rough Operations and Uncertainty Measures on MV-Algebras - Maosen Xie (Journal of Applied Mathematics)
We define a lower approximate operation and an upper approximate operation based on a partition on MV-algebras and discuss their properties. We then introduce a belief measure and a plausibility measure on MV-algebras and investigate the relationship between rough operations and uncertainty measures.